2011
DOI: 10.1021/bi200595z
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Conformational Changes in Photosynthetic Reaction Centers: Impact of Detergents and Lipids on the Electronic Structure of the Primary Electron Donor

Abstract: Light-induced hypsochromic shifts of the Q(y) absorption band of the bacteriochlorophyll dimer (P) from 865 to 850 nm were identified using continuous illumination of dark-adapted reaction centers (RCs) from Rhodobacter capsulatus when dispersed in the most commonly used detergent, the zwitterionic lauryl N-dimethylamine-N-oxide. Such a shift is known to be the consequence of the decreased degree of delocalization of P. A 2-fold acceleration of the recovery kinetics of P(+) was found in RCs that underwent ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 73 publications
4
11
0
1
Order By: Relevance
“…19 The degree of delocalization of the electron hole on P + has already been proposed, among other structural factors, as playing a role in the stabilization of P + Q A − following photoexcitation on the minute time scale. 70 The notion that reorganization of the protein around P + plays a role in stabilizing charge separation on the long time scale is also in line with recent studies performed in mutant RCs, characterized by different H-bonding patterns of the P dimer. Interestingly, evidence of a lightinduced change of the local dielectric constant in the vicinity of the P dimer has been provided, 12 and proton release by one or more amino acid residues, mainly involving water molecules near P, has been proposed as the relaxation event which stabilizes the charge separated state on a long time scale.…”
Section: Implications For the Stability Of The Primary Charge Separat...supporting
confidence: 73%
See 1 more Smart Citation
“…19 The degree of delocalization of the electron hole on P + has already been proposed, among other structural factors, as playing a role in the stabilization of P + Q A − following photoexcitation on the minute time scale. 70 The notion that reorganization of the protein around P + plays a role in stabilizing charge separation on the long time scale is also in line with recent studies performed in mutant RCs, characterized by different H-bonding patterns of the P dimer. Interestingly, evidence of a lightinduced change of the local dielectric constant in the vicinity of the P dimer has been provided, 12 and proton release by one or more amino acid residues, mainly involving water molecules near P, has been proposed as the relaxation event which stabilizes the charge separated state on a long time scale.…”
Section: Implications For the Stability Of The Primary Charge Separat...supporting
confidence: 73%
“…8,10 The conclusion that the kinetics of P + Q A − recombination after a short (ns) light pulse are not affected by the asymmetry of charge distribution within the P + dimer does not exclude, however, that this parameter may influence the conformational RC rearrangements occurring upon continuous illumination on the second to minute time scale, and resulting in a dramatic stabilization of the charge separated state of the RC. 11,14,15,69,70 We have recently observed 16 that the response to dehydration of the P + Q A − recombination kinetics after a prolonged illumination (20 s) is markedly different from that observed after a short photoexcitation. 16,29 In particular, we found that in RC films dehydrated at r = 76%, continuous photoexcitation resulted in the appearance of an extremely slow phase of P + Q A − recombination, with a lifetime τ AP ≈ 8 s, accounting for about 50% of the decay.…”
Section: Implications For the Stability Of The Primary Charge Separat...mentioning
confidence: 99%
“…In the near-infrared region, it comprises three main bands that arise from the bacteriochlorin cofactors (Figure 1 B ), the relative intensities and wavelength maxima of which are known to be modulated somewhat by the detergent/lipid environment of the protein. 13 , 14 The SMA-solubilized RCs had an absorbance spectrum that was similar to that of RCs in native membranes or solubilized in either LDAO or DDM, showing that it is structurally intact in the SMA/lipid nanodiscs (Figure 1 B ). Small differences in intensity of the bands at 865 and 760 nm in the four preparations are a consequence of the sensitivity of cofactors at, or close to, the surface of the protein to its detergent/lipid environment.…”
mentioning
confidence: 86%
“…[12] However, such applications require the preparation of large amounts of protein that is structurally stable and optimally active. This presents challenges because the functional properties of the RC are known to be modulated when it is removed from the native membrane, [13][14][15] and its stability is known to be dependent on the detergent/lipid environment. [16] To determine the usefulness of the SMA copolymer as a new vehicle for housing integral membrane proteins such as RCs, the properties of SMA-purified RCs were systematically compared with those of RCs purified in the commonly used detergents N,N-dimethyldodecylamine N-oxide (LDAO) and n-dodecyl b-d-maltoside (DDM), as well as with those of RCs in intact native photosynthetic membranes.…”
mentioning
confidence: 99%